استخدام مدونة الفيديو وفعاليتها في تحسين مهارة الكلام لدى الطلبة الناطقين بغير العربية في ماليزيا - Nur Hanisah binti Hashim (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
The research is to investigate the use of video blogging and its effectiveness in improving speaking skills among non-Arabic students at the Centre for Languages and Pre-Academic Development (CELPAD) of the International Islamic University Malaysia at an advanced level in Quranic Language. The objectives of this research are to explain how video blogging is used in the learning process, to determine if the there is a significant difference between the two tests in speaking skills, identify the students' attitudes towards improving speaking skills through video blogging and identify how students' performance is improved through video blogging based on their grades in the post-test. The research was based on a semi-empirical approach, where the researcher analysed the scores of a group of 21 students in preliminary and post speaking skill tests. Paired Sample T-Test was used to analyse the two tests and the tool used in the treatment process was making Arabic video blogs in three weeks. A questionnaire on students' attitudes towards the video blogging was given at the end of the research and was analysed with Pearson's Correlation Coefficient Test. The result shows that there were statistically significant differences between the mean scores of the preliminary and post-tests, and there was no statistically significant relationship between the students' attitudes and their grades in the post test. Therefore, the study found that video blogging is not directly related to students' attitudes but may contribute in improving Arabic speaking skills among non-native speakers.